2006
DOI: 10.1902/jop.2006.050247
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinus Septa: Prevalence, Height, Location, and Morphology. A Reformatted Computed Tomography Scan Analysis

Abstract: It can be inferred that there is a wide anatomical variation in the prevalence, size, location, and morphology of maxillary sinus septa, irrespective of the degree of atrophy. Therefore, to prevent the likelihood of complications arising during sinus augmentation procedures, a thorough and extensive understanding of the anatomic structures inherent to the maxillary sinus is indispensable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
165
7
20

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(209 citation statements)
references
References 16 publications
17
165
7
20
Order By: Relevance
“…Results from our present study revealed that sinus septa were observed in 55.2% of the 270 sinuses. The prevalence of sinus septa found by Güncü et al 13 was 16.1%, by Krennmair et al 18 was 16%, and by Kim et al 19 was 26.5% when CT was used to assess the sinuses. These results are not consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 87%
“…Results from our present study revealed that sinus septa were observed in 55.2% of the 270 sinuses. The prevalence of sinus septa found by Güncü et al 13 was 16.1%, by Krennmair et al 18 was 16%, and by Kim et al 19 was 26.5% when CT was used to assess the sinuses. These results are not consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 87%
“…The occurrence and location of maxillary sinus septa have been evaluated using panoramic radiography, CT and CBCT 3,15,[19][20][21] . Significant differences in the septum angle were noted between the anterior maxillary sinus and transverse palatine suture regions 3) .…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to that reported in the dentate maxilla of some previous studies [1][2][3] . The mean septal height was reported to be from 3.55 to 9.2 mm on CT examination 3,15,19,20) . The mean height (2.1 mm, s.d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas relaciones anatómicas pueden variar dependiendo del grado de neumatización del seno maxilar, si-tuación que se ve exacerbada al perder un diente, describiéndose neumatizaciones tanto hacia la pared anterolateral del seno como también hacia la tuberosidad del maxilar. De este modo la altura del proceso alveolar se ve alterada tanto por la reabsorción alveolar como también por la neumatización del seno maxilar (Gosau et al;Kim et al, 2006;Lee et al;Maestre-Ferrín et al, 2010;Raja).…”
Section: Introductionunclassified